1120. Impact of Training Residents to Improve HIV Screening in a Teaching Hospital in Mexico City. (31st December 2020) - Guerrero-Torres, Lorena; Núñez-Saavedra, Isaac; Caro-Vega, Yanink; Crabtree-Ramírez, Brenda
Abstract: Background: Among 230, 000 people living with HIV in Mexico, 24% are unaware of their diagnosis, and half of newly diagnosed individuals are diagnosed with advanced disease. Early diagnosis is the goal to mitigate HIV epidemic. Missed opportunities may reflect a lack of clinicians' consideration of HIV screening as part of routine medical care. We assessed whether an educational intervention on residents was effective to 1) improve the knowledge on HIV screening; 2) increase the rate of HIV tests requested in the hospitalization floor (HF) and the emergency department (ED); and 3) increase HIV diagnosis in HF and ED. Methods: Internal Medicine and Surgery residents at a teaching hospital were invited to participate. The intervention occurred in August 2018 and consisted in 2 sessions on HIV screening with an expert. A questionnaire was applied before (BQ) and after (AQ) the intervention, which included HIV screening indications and clinical cases. The Institutional Review Board approved this study. Written informed consent was obtained from all participants. BQ and AQ scores were compared with a paired t-test. To evaluate the effect on HIV test rate in the HF and ED, an interrupted time series analysis was performed. Daily rates of tests were obtained from September 2016 to August 2019 and plotted along time. Restricted cubic splines (RCS) were used to model temporal trends. HIV diagnosis in HF and ED pre- and post-intervention were compared with a Fisher's exact test. A p< 0.05 was considered significant. Results: Among 104 residents, 57 participated and completed both questionnaires. BQ score was 79/100 (SD±12) and AQ was 85/100 (SD±8), p < .004. Time series of HIV testing had apparent temporal trends (Fig 1). HIV test rate in the HF increased (7.3 vs 11.1 per 100 episodes) and decreased in the ED (2.6 vs 2.3 per 100 episodes). HIV diagnosis increased in the HF, from 0/1079 (0%) pre-intervention to 5/894 (0.6%) post-intervention (p< .018) (Table 1). Fig 1. HIV test rates. Gray area represents post-intervention period. Table 1. Description of episodes, HIV tests and rates pre- and post-intervention in the Emergency Department and Hospitalization Floor. Conclusion: A feasible educational intervention improved residents' knowledge on HIV screening, achieved maintenance of a constant rate of HIV testing in the HF and increased the number of HIV diagnosis in the HF. However, these results were not observed in the ED, where administrative barriers and work overload could hinder HIV screening. Disclosures: All Authors : No reported disclosures